Determinants of Weight Increase and Menstrual Cycle Irregularities in KB Implant Acceptors in Pematang Cengal, Tanjung Pura District - Ria Julita Sari; Rini Susanti; Sudarianti (PT Inovasi Pratama Internasional, 2023)
Based on data from the World Health Organization or WHO and the Central Statistics Agency, the use of contraceptives in 2022 will increase. It is recorded that in 2022 there are around 55.36% of fertile couples using these contraceptives, an increase of 0.30% from 2021. One of the commonly used contraceptive methods is the implant method which is included in the long-term contraceptive method. This method will be applied to the subdermal area containing progestin with a fairly long acting. In addition, the dose is low and reversible for women. The effectiveness of the use of implant contraception is quite high. And can be used in the long term and restore the fertility rate of women who will quickly return and affect the hormone estrogen. This research was conducted to find out and obtain data and information regarding the relationship between weight gain and changes in the menstrual cycle that occur in women using implant contraception in the Pematang Cengal area, Tanjung Pura District. The population in this study were KB Implant acceptors who were in the area. The research method used in this study used group data collection from a population of around 50 people. It is hoped that respondents and informants can obtain information regarding the relationship between weight gain and changes in the menstrual cycle.